2017
DOI: 10.1111/cei.12911
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokine interferon-γ and microbiome-derived metabolites dictate epigenetic switch between forkhead box protein 3 isoforms in coeliac disease

Abstract: SummaryCoeliac disease (CD) is an autoimmune enteropathy triggered by gluten and characterized by a strong T helper type 1 (Th1)/Th17 immune response in the small intestine. Regulatory T cells (T reg ) are CD4 1 CD25 11 forkhead box protein 3 ( FoxP3 1 ) cells that regulate the immune response. Conversely to its counterpart, FoxP3 full length (FL), the alternatively spliced isoform FoxP3 D2, cannot properly down-regulate the Th17-driven immune response. As the active state of CD has been associated with impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 56 publications
1
43
0
2
Order By: Relevance
“…26 Butyrate, a short chain fatty acid produced by commensal bacteria of the human intestine, was already used to induce oxidative stress and apoptosis in CaCo2 cell cultures in Fauser et al 27 Moreover, it was reported that butyrate could act as an epigenetic "switch" of the immune system. 28 Butyric acid has been in fact associated with the ability to inhibit histone deacetylases (HDAC), and favors a state of acetylated histones in the cell. 29 DMSO is a powerful oxidant that is oen used as a solvent in various experimental tests and in NMR analysis, while its signals have low interferences, and it can dissolve a large number of substances.…”
Section: Resultsmentioning
confidence: 99%
“…26 Butyrate, a short chain fatty acid produced by commensal bacteria of the human intestine, was already used to induce oxidative stress and apoptosis in CaCo2 cell cultures in Fauser et al 27 Moreover, it was reported that butyrate could act as an epigenetic "switch" of the immune system. 28 Butyric acid has been in fact associated with the ability to inhibit histone deacetylases (HDAC), and favors a state of acetylated histones in the cell. 29 DMSO is a powerful oxidant that is oen used as a solvent in various experimental tests and in NMR analysis, while its signals have low interferences, and it can dissolve a large number of substances.…”
Section: Resultsmentioning
confidence: 99%
“…show that regulatory T cells from CD patients are impaired in their ability to suppress the proliferation of CD4 + CD25 − responder cells after CD3/CD28 co‐stimulation in comparison to regulatory T cells from healthy individuals (Figure c). In their study, Serena et al . demonstrate overexpression of the alternatively spliced isoform of FoxP3 in CD mucosa.…”
Section: The Interaction Of α‐Gliadin and Its Proteolytic‐resistant Pmentioning
confidence: 90%
“…Studies thus suggest the imperative interaction of intestinal bacteria with immune system to direct the differentiation of both pro-inflammatory and anti-inflammatory T cell populations ( Round and Mazmanian, 2009 ). The role of Regulatory T cells (Treg) has become clearer with the efforts of Serena et al (2017) that help us to understand the pathogenic role of gut microbiota and their metabolites in CD through epigenetic processes. Treg cells are subset of CD4 T cells responsible for maintaining immune response to foreign antigens ( Lehtimäki and Lahesmaa, 2013 ).…”
Section: Microbes In Pathogenesis Of CDmentioning
confidence: 99%
“…Ex-vivo cultures of intestinal biopsies treated with butyrate trigger a balance between FoxP3 isoforms in HC subjects, while the same does not occur in CD patients. That shows the role of microbial metabolites in modulation of splicing, thus triggering to an inflammatory state with some role in pathogenesis of CD ( Serena et al, 2017 ).…”
Section: Microbes In Pathogenesis Of CDmentioning
confidence: 99%
See 1 more Smart Citation